A Stylistic Analysis of Ndidi Chiazor-Ememnor’s If They Tell The Story (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
This research is a stylistic analysis of Ndidi Chiazor-Enenmor’s 2020 novel, If They Tell the Story. The study notes that writers use language in a peculiar way which makes them different from others. This peculiarity in writing constitutes a writer’s style. A writer's unique style reflects their ideological point of view and leads the reader to their stance on a particular issue. Style is the soul of the embedded meanings in a literary piece. The analysis of linguistic style in poetry has been the major concern of most language scholars over the years. However, there is little attention given to the linguistic description of the style in prose forms, especially the style of authors of recent novels. It is against this background that the research was undertaken to examine linguistic stylistic features in Ndidi Chiazor-Enenmor’s If They Tell the Story and also assess how these features are foregrounded as well as the way they help to convey the ideas in the novel. The theoretical framework deployed for the work is foregrounding theory propounded by Mukarovský (1970). This study reveals that the stylistic features used by the author are morphological foregrounding, graphological foregrounding, and syntactic foregrounding. The study concludes that the use of these linguistic features is not only for aesthetic purpose but also to facilitate the conveyance of the message which the author has for the readers.
Keywords: stylistics; foregrounding; Jan Mukarovský; morphology; graphology; semantics